2017
DOI: 10.1136/bjophthalmol-2016-310074
|View full text |Cite
|
Sign up to set email alerts
|

Polypoidal choroidal vasculopathy: a common type of neovascular age-related macular degeneration in Caucasians

Abstract: The prevalence of PCV in Caucasians is higher than previously reported. Indocyanine Green Angiography should be a standard investigation for all new patients with NAMD, particularly those with occult NAMD, to avoid missing this important subset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 18 publications
1
42
0
2
Order By: Relevance
“…The presenting characteristics of serous retinal detachment (in 66.7%) and subretinal hemorrhage (in 37%) in this study of PCV in Caucasian patients were very similar to those reported in a large study on Japanese patients, 52% of whom were found to have serous macular detachment and 30% of whom had submacular hemorrhage [27]. Although the highest prevalence of PCV has been noted in Asian countries and populations [3], it has been recently recognized more frequently in Caucasian patients when using ICGA with the SLO for the evaluation of exudative AMD [13][14][15][16][17]. In a study in Brazil on patients of mostly European descent, the prevalence of PCV in Caucasian patients with exudative AMD was 24.5% [14].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The presenting characteristics of serous retinal detachment (in 66.7%) and subretinal hemorrhage (in 37%) in this study of PCV in Caucasian patients were very similar to those reported in a large study on Japanese patients, 52% of whom were found to have serous macular detachment and 30% of whom had submacular hemorrhage [27]. Although the highest prevalence of PCV has been noted in Asian countries and populations [3], it has been recently recognized more frequently in Caucasian patients when using ICGA with the SLO for the evaluation of exudative AMD [13][14][15][16][17]. In a study in Brazil on patients of mostly European descent, the prevalence of PCV in Caucasian patients with exudative AMD was 24.5% [14].…”
Section: Discussionsupporting
confidence: 80%
“…PCV is a subtype of exudative AMD which has been underrecognized in Caucasian populations, often due to the lack of imaging with ICGA in occult choroidal neovascularization associated with AMD [16,17]. A recent increase in the prevalence of PCV in exudative AMD in Caucasian patients, i.e., from 20 to 31%, has been reported [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations